Modelling of sediment wedge movement along low-angle detachments using ABAQUS™ - Tuitt, A.; King, R.; Hergert, R.; Tingay, Mark; Hillis, R. (Geological Society Publishing House, 2012)
Delta-deepwater fold-thrust belts (DDWFTBs) develop over low-angle detachment faults which link extension to downslope contraction. Detachment faults have been examined in previous studies for the Amazon Fan, Niger, Nile, Angola, Baram and Bight Basin DDWFTBs. The driving mechanisms for the movement along the detachment remain uncertain, however. Previous authors have attributed the movement along detachment faults to high pore-fluid pressure, which reduces the effective normal stress acting on a fault surface thereby encouraging sliding along the fault. However, high pore-fluid pressure has not been directly confirmed in many of these faults due to a lack of well data in detachment surfaces. In this study, finite element modelling was used to test the effects of pore-fluid pressure, coefficient of friction, sediment rigidity and sediment wedge angle on sliding along the detachment. The modelling suggests that increased pore-fluid pressures and decreased coefficients of friction increase slip along a detachment. At hydrostatic pore-fluid pressures, sediment rigidity and sediment wedge angle have relatively little effect on the movement of the sediment wedge along the detachment. Modelling of these conditions using ABAQUSTM improves our understanding of the nature and mechanics of DDWFTBs and their underlying detachments.